A unique signal sequence of the chemokine receptor CCR7 promotes package into COPII vesicles for efficient receptor trafficking. Issue 2 (30th March 2018) - Uetz‐von Allmen, Edith; Rippl, Alexandra V.; Farhan, Hesso; Legler, Daniel F.
Abstract: Chemokine receptors are considered to belong to the group of G protein‐coupled receptors that use the first transmembrane domain as signal anchor sequence for membrane insertion instead of a cleavable N‐terminal signal sequence. Chemokine recognition is determined by the N‐termini of chemokine receptors. Here, we show that the chemokine receptor CCR7, which is essential for directed migration of adaptive immune cells, possesses a 24 amino acids long N‐terminal signal sequence that is unique among chemokine receptors. This sequence is cleaved off the mature human and mouse protein. Introducing single point mutations in the hydrophobic core h‐region or in the polar C‐terminal segment (c‐region) of the signal sequence to interfere with its cleavage retained CCR7 in the ER and prevented its surface expression. Furthermore, we demonstrate the correct topology of the 35 amino acids short extracellular N‐tail of CCR7 in a deletion mutant lacking the natural signal sequence. This signal sequence deletion mutant of CCR7 is fully functional as it efficiently binds its ligand, elicits chemokine‐induced calcium mobilization, and directs cell migration. However, we show that the signal sequence promotes efficient recruitment of the GPCR to ER exit sites, thereby controlling efficient ER to Golgi trafficking of CCR7 on its way to reach the plasma membrane. Abstract : A unique cleavable signal sequence among chemokine receptors regulates CCR7 trafficking along the secretory pathway by facilitating coupling to the ER export machinery.